Structural Components of Creative Potential of University Pedagogical Personnel - Isyanova, Alfia; Usmanova, Shoira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the specifics of professional activity of pedagogical personnel and structural components of creative potential have been marked; specific statistically significant criteria of evaluation have been found out, pedagogical reserves of educational process of improving and developing of creative potential of pedagogical personnel. Conditionally components of creative potential of pedagogical personnel have been marked, creative potential of pedagogical personnel have been evaluated. Pedagogical Pedagogical of educational process of improving and developing of creative potential of pedagogical personnel have been offered.